PKM Pendampingan Perempuan Penenun Berbasis Budaya Lokal melalui Self Control - Fahimah, Siti; Alfiyah, Avif (GUYUB: Journal of Community Engagement, 2023)
Women are the pillars of life, especially in domestic matters, this condition makes them have to take roles in the domestic and public spheres at the same time. in the public sector, forcing them to do various jobs, such as farmers, fishermen and weavers. They choose weaving because they don't have other jobs, they don't have much education, and they don't have much capital. For women, working is helping the poor household economy. This assistance was carried out in Laren Lamongan Pelangwot Village. The method used is ABCD (Asset Based Community Development) because the Pelangwot residents have looms and the process of making woven sarongs is a village asset. The results of this assistance show that women are able to start organizing their lives better and have the fighting power to develop their creativity in weaving, this is shown in their behavior during the counseling and training carried out, not only that, they also ask for further assistance to strengthen their community so that it can be formally recognized.